Creating Paper Robots increases designers' confidence to prototype with microcontrollers and electronics. Issue 1 (3rd April 2017) - Analytis, Santhi; Sadler, Joel A.; Cutkosky, Mark R.
Abstract: This article describes a creative design activity to introduce engineering students to mechatronic prototyping. Our goal was to find a creative task to increase student confidence and skills in mechanical design, electrical circuits, microcontrollers, and programming. We present the Paper Robot exercise, a design activity that blends everyday materials such as cardboard, with electronic components. This activity was introduced during the 2010–2011 academic year and has been repeated every year since, in a global, industry-sponsored design course at Stanford University. The Paper Robot exercise resulted from the observation that students were intimidated to create functional prototypes with microcontrollers. The teaching team needed a way to quickly introduce tools for programming electronic components and to encourage creative experimentation early in the course. Results include a 100% task performance rate of students that successfully made a robot meeting the minimum requirements. 76% of students reported an increase in knowledge in programming microcontrollers (Arduino), and 69% increased their knowledge in creating electronic circuits out of raw components. This activity may be modified to introduce younger students to mechatronic platforms in STEM education curriculum.